Membangun Customer Loyalty pada Bank Komersial: Peran Mediasi Trust dalam Relationship Quality dan Customer Intimacy - Jefry Akbar Izul Haq; Mochamad Nurhadi; Reza Tianto; Mochamad Anang Karyawan (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study is driven by digital transformation and the rapid growth of financial technology, which have increased customer expectations and intensified competition in the banking industry, making customer loyalty more difficult to maintain. Therefore, relationship quality and customer intimacy are considered crucial in building trust as the foundation of customer loyalty. This study examines the effects of relationship quality and customer intimacy on customer loyalty, with trust as a mediating variable among commercial bank customers in Surabaya and its surrounding areas. A quantitative approach with an explanatory research design was employed, involving 150 respondents who were selected through purposive sampling. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented in SmartPLS 4.0. The results show that relationship quality and customer intimacy have positive and significant effects on both trust and customer loyalty, while trust also exerts a significant effect on customer loyalty. Furthermore, trust partially mediates the relationship between relationship quality and customer loyalty, but does not mediate the relationship between customer intimacy and customer loyalty. These findings suggest that customer loyalty is shaped through both a trust-based (cognitive) pathway and an emotional closeness pathway. Therefore, banks should strengthen relationship quality and enhance personalized services to foster stronger customer loyalty.